New Development of a Solar Electrochemical Raceway Pond Reactor for Industrial Wastewater Treatment - Salazar-Gonzalez, R; Toro-Campos, S; Toro-Campos, S; Calzadilla-Aguiar, W; Calzadilla-Aguiar, W (Academic Press, 2022)
In this work, a solar electrochemical-raceway pond reactor (SEC-RPR) is used to treat textile industrial wastewater by solar photoelectron-Fenton (SPEF) at pilot plant scale for the first time. The SEC-RPR is composed of an electrochemical filter press-cell coupled to RPR, where H2O2 is electro-generated. A complete study about experimental variables such as current, catalyst concentration, pollutant load or liquid depth is conducted based on methyl orange removal, mineralization and decolorization. Validation of the SPEF process using SEC-RPR reached more than 80% of mineralization, as well as the complete decolorization of the solution. The good performance of the SPEF treatment in the new SEC-RPR led to quick degradation kinetics, mainly due to the synergetic action of solar radiation and good distribution of H2O2 electrogenerated in the photoreactor. 100% Methyl Orange degradation was achieved after 150, 60, 45, 30 and 20 min of reaction time applying current density equal to 5, 10, 20, 40 and 60 mA cm−2, respectively. However, the increase of current density decreased the mineralization current efficiency. Up to 10 aromatics intermediates and 5 short-chain carboxylic acids were identified by LC-MS and HPLC analysis and a reaction pathway for MO mineralization by SPEF is proposed. This study represents an essential preliminary step towards the development of the first SEC-RPR at demo scale. © 2022 Elsevier Inc.